Optimizing Value Added Tax (VAT) Revenue in Indonesia - Zuhad, Fariz; Wisang Christandriya, Garnetto; Idha Prihatini, Natalia (Jurnal Justice Dialectical, 2024)
This paper discusses the Optimization of Value Added Tax (VAT) Revenue in Indonesia, highlighting the importance of taxes as a source of funding for the state. Taxes serve as a tool to support national development and meet the needs of society. In this context, VAT becomes one of the largest sources of tax revenue after Income Tax (PPh), contributing approximately 30% of total tax revenue.Changes in tax regulations, particularly through the Draft Law on Harmonization of Tax Regulations (HPP), have sparked controversy in society, especially concerning the increase in VAT rates from 10% to 12% and the introduction of a multi-rate scheme. This paper also identifies factors that hinder the optimization of VAT revenue, including taxpayer compliance and operational costs of the tax system. An analysis is conducted on the impact of tax policy on the economy and the effectiveness of tax collection in supporting national financial stability.By understanding the dynamics and challenges in VAT revenue collection, it is hoped that solutions can be found to enhance tax contributions to national development.